TRADISI AYUN BUDAK PADA MASYARAKAT BANGUN PURBA DI KABUPATEN ROKAN HULU - ", Suaibah; Asriwandari, Hesti (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2014)
Ayun budak is one of tradition in Bangun Purbaâs society wich is full at purposes andrelegius value. The main purpose of this procession is expression of gratitude to god becausea new family member is born. This gratitude is expressed in song lyrics that is sing.This Ayun Budak procession is always delivering aqiqah at a new born child so thatcutting hair, tepung tawar baby with his/ her parents are always beginning this procession.Then, a baby is put in a swing and rock him/her.while singing soft and melodious song. Thesinging is bigger than usual and decorate with paper, ribbor or colourfl material.This is a descriptive kualitatif research. This research is oriented from spradleyresearch wich are : (1) deciding the research object, (2) doing field research, (3) doing themeanaliysis, (4) writing the report.The informan of this research are : (1) Dalian Natolu group, (2) religious group, (3)smart people group, (4) singer ayun budak song (5) government local group, (6) holdingceremony group.The result of this research shows that ayun budak event has some puposes : (a) asgratitude to god because a new family member is born safely and healthy, (b) ayun budakbecome media to deliver advices to the baby or participant, (c) ayun budak and the songconcist of prayer to Allah, (d) the processios of ayun budak can buid relationship among thesociety.The writer conclude that since in motherâs womb the child is delivered and in thechildâs grow, ther is education effort in family wich is a manifestation at a man gift.Keyword: Ayun Budak, Tradition in Bangun Purba, Society Rokan Hulu Riau